Perkembangan dan Permasalahan Teorisasi Hubungan Internasional Pasca Perdebatan - Mantra, Dodi (Universitas Muhammadiyah Yogyakarta, 2015)
There are two contradictory narratives those enframe the contemporary development of International Relations (IR) theory. As the absence and discontinuity of the so-called â€œinter-paradigm debatesâ€, the first narrative enframes the contemporary development of IR theory is moving toward its end. On the contrary, the other narrative celebrates the plurality of theoretical development in contemporary IR, and letting â€œa thousand theoretical flowers bloomâ€. This article seeks to reveal that both of these narratives are problematic. The main problem of the first narrative lies in the â€œdebatismâ€ approach as the basis of its historiography. This article shows how the â€œdebatismâ€ approach misrepresents the history of IR theorization. Meanwhile, the second narrative is problematic as well, since the celebration of theoretical plurality tends to neglect the philosophical foundations and concentrate on the technical side of theorization. Drawing on Fred Chernoffâ€™s steps of IR theorization, this article proposes a new frame of IR theorization in order to leave behind the problematic â€œdebatismâ€ approach, while proliferate â€œa thousand of theoretical flowers bloomâ€ without neglecting the importance of philosophical foundations in IR theorization.